International Transportation of Nuclear and Radioactive Materials through the Lombok Strait as Indonesian Archipelagic Sea Lane - Muhammad Sujana Prawira; Rahmat Edhi Harianto (Faculty of Law Universitas Sebelas Maret, 2024)
A literature review has been carried out to determine international and national legal frameworks regarding international transportation of nuclear and radioactive materials through the Lombok Strait in Indonesia. The Lombok Strait is one of the Indonesian Archipelagic Sea Lanes which has been regulated both in the national and international legal frameworks as a pathway between two oceans that passes through Indonesian waters. Transportation of goods by ship is passage of innocent as stated in Sea Law Convention. However, due to nuclear and radioactive materials are not ordinary goods, the safety and security of nuclear and radioactive materials should be ensured. The paper examines Indonesian national laws on nuclear and radioactive materials transport through Lombok Strait. Review results that apart from the carrier should comply with national and international legal frameworks, coordination between governmental agencies in Indonesia including local governments plays an important role in the innocent passage through the Lombok Strait. Finally, ensuring nuclear and radioactive materials transports are safe and secure in the context of international shipment is a necessity to ensure safety and security for workers, public and the environment.Keywords: Lombok Strait; nuclear; transport.